Rancang Bangun Mesin Pencacah Plastik Sebagai Bahan Baku Mesin Pirolisis Skala Komunal - Mochamad Syamsiro; Arip Nur Hadiyanto; Zahrul Mufrodi (Universitas Janabadra, 2016)
Design and fabrication of plastic shredding machine has been conducted to supply the feedstock for pyrolysis of waste plastics to produce liquid oil. The machine has a capacity of 20-30 kg/h depending on the plastic type and thickness. We propose the integrated system for pyrolysis of waste plastics in small or medium scale which utilize our product as a source of energy for pyrolysis and shredding machine. The gaseous and solid products can be used for pyrolysis while the liquid oil will be used for powering the shredding machine. The excess liquid oil can be used as a fuel for household and small enterprise by employing pressurized cooking stove. The preliminary test shows that the shredding machine can be used for crushing PET bottle smoothly with the capacity of 14 kg/h. The capacity can be increased by adding the material input and by employing water to push the shredded plastic flowing down.